Risk-Pooling Essentials: Reducing Demand and Lead Time Uncertainty - Oeser, Gerald (Springer, 2015)
This book provides comprehensive and concise definitions of risk pooling and risk-pooling methods, a straightforward statistical explanation, and a value-chain oriented framework for analyzing risk-pooling methods. Risk pooling mitigates demand and lead time uncertainty in logistics and supply chain management. The author also provides readers with a downloadable computerized decision support tool to compare and choose appropriate risk-pooling methods and to apply them in companies. Students and practitioners of logistics and supply chain management will find this book particularly useful.